Application of Military Law Against TNI Members Who Commit Desertion Crimes - Aswin Nugraha Sailellah (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
This study aims to: 1) To analyze the application of military criminal law against members of the TNI perpetrators of desertion crimes; 2) To analyze the constraints in the enforcement of miiliter criminal law against members of the TNI perpetrators of desertion crimes. This study uses normative-empirical legal research, while the data analysis used is qualitative approach to primary data and secondary data. where in analyzing / processing data first held organizing of primary data obtained through related legislation and literature. Then the collected data is then discussed, compiled, elaborated, and interpreted, and reviewed the problem so that a conclusion is obtained as a problem solving effort. The results showed that the application of military criminal law against members of the TNI who were proven to commit desertion crimes is the authority of the military judiciary to prosecute him, then the stages in the form of investigations conducted by the Military Police on the orders of the Superior Who Has the Right to Punish (Ankum). furthermore, the investigation file is given to the Military Oditur to be studied, then the military oditur makes an indictment to be delegated to the Military Judiciary, after the judiciary feels sufficient with the files of the Military Oditur, then the military judiciary will prosecute members of the military who are accused of desertion. Furthermore, constraints in law enforcement related to desertion crimes are reviewed from 4 interrelated aspects, namely with regard to legal subtansi, the legal structure itself, facilities or infrastructure, and the community. The settlement of cases in the military judiciary at this time has been well arranged, but it is expected that all who play a role in the process of resolving military cases do all these stages based on Justice and Positive Law. The application of existing regulations must be done consistently and always conducted a review of desertion cases so that from these obstacles can be found solutions and solutions to reduce the quantity of desertion crimes.